Munchausen syndrome by proxy. Causes, signs and treatment - Majda, Katarzyna; Dudzik, Katarzyna; Jarząbkowska, Angelika; Łakomska, Oliwia (Journal of Education, Health and Sport, 2019)
Violence against children is a common issue as well known as in Poland and the whole world. The main problem that occurs is domestic violence, which in most of the cases remains unreported, due to the shame, fear, relationship and the lack of a victim awareness. Among the maltreatment we can name three most prevalent; shocked children syndrome, sexual abuse of a child and the Munchausen syndrome by Proxy (MSbP). The purpose of this article is to describe the causes and effects of this dangerous disorder, where children become victims. We need to bare in mind that all people who interacts with children, for instance; doctors, teachers, psychologists, pedagogues may struggle this issue. Moreover they should also have knowledge about the health and surrounding conditions of a particular child. Thanks to understanding the acting of the mothers, who suffer from MSbP, we can not only protect children from further maltreatment, but also prevent them from complications and deaths. Furthermore, it will increase the probability of a medical help for mothers, like psychiatric and psychological treatment. The MSbP is a special form of the violence – a parent to gain the attention and compassion of the surrounding is able to make a physical and emotional harm to a child. There also appears the threat of child’s life, hospitalization and more over potentially harmful medical activities, not only to healthy children, but also chronically ill. As a result it may cause to exacerbation of the disease process and even more to death of a child if we could not spot the difference between the real and fabricated symptoms made by caregivers.